Associations of Mitochondrial Fatty Acid Oxidation with Body Fat in Premenopausal Women - Jonathan L. Warren; Barbara A. Gower; Gary R. Hunter; Samuel T. Windham; Douglas R. Moellering; Gordon Fisher (Journal of Nutrition and Metabolism)
Higher in vivo fatty acid (FA) oxidation rates have been reported in obese individuals compared to lean counterparts; however whether this reflects a shift in substrate-specific oxidative capacity at the level of the skeletal muscle mitochondria has not been examined. The purpose of this study was to test the hypothesis that in situ measures of skeletal muscle mitochondria FA oxidation would be positively associated with total body fat. Participants were 38 premenopausal women (BMI=26.5±4.3 kg/m2). Total and regional fat were assessed by dual-energy X-ray absorptiometry (DXA). Mitochondrial FA oxidation was assessed in permeabilized myofibers using high-resolution respirometry and a palmitoyl carnitine substrate. We found positive associations of total fat mass with State 3 (ADP-stimulated respiration) (r=0.379, p<0.05) and the respiratory control ratio (RCR, measure of mitochondrial coupling) (r=0.348, p<0.05). When participants were dichotomized by high or low body fat percent, participants with high total body fat displayed a higher RCR compared to those with low body fat (p<0.05). There were no associations between any measure of regional fat and mitochondrial FA oxidation independent of total fat mass. In conclusion, greater FA oxidation in obesity may reflect molecular processes that enhance FA oxidation capacity at the mitochondrial level.